2009
DOI: 10.1016/j.jconrel.2009.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Targeted lipid-coated nanoparticles: Delivery of tumor necrosis factor-functionalized particles to tumor cells

Abstract: Polymeric nanoparticles displaying tumor necrosis factor on their surface (TNF nanocytes) are useful carrier systems capable of mimicking the bioactivity of membrane-bound TNF. Thus, TNF nanocytes are potent activators of TNF receptor 1 and 2 leading to a striking enhancement of apoptosis. However, in vivo applications are hampered by potential systemic toxicity. Here, using TNF nanocytes as a model system, we developed a procedure to generate targeted lipid-coated particles (TLP) in which TNF activity is shie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 125 publications
0
71
0
1
Order By: Relevance
“…34,37,41,42 Briefly, all lipids were mixed in a round bottom flask and dissolved in chloroform:methanol (9:1 v/v). A thin and uniform lipid film was obtained by evaporating the solvents under pressure for 30 minutes at 42°C.…”
Section: 40mentioning
confidence: 99%
See 1 more Smart Citation
“…34,37,41,42 Briefly, all lipids were mixed in a round bottom flask and dissolved in chloroform:methanol (9:1 v/v). A thin and uniform lipid film was obtained by evaporating the solvents under pressure for 30 minutes at 42°C.…”
Section: 40mentioning
confidence: 99%
“…The mixture was then extruded 17-20 times under pressure through a series of polycarbonate filters ranging from 200 to 50 nm to obtain a uniform suspension of particles. Size and polydispersity index (PDI) 31,34,41,43 were determined by dynamic light scattering 43 on a Zetasizer ® Nano ZS (Malvern Instruments, Worcestershire, UK). Liposomes were subjected to Rouser phosphate assay 44 where phospholipid was determined and a total lipid amount was calculated after cholesterol correction.…”
Section: 40mentioning
confidence: 99%
“…8). 109 Thus, TNF nanocytes are potent activators of TNF receptors 1 and 2 leading to a striking enhancement of apoptosis. However, in vivo applications are hampered by potential systemic toxicity.…”
Section: Surface Modification By Antibodiesmentioning
confidence: 99%
“…Recently, Noble et al demonstrated that immunoliposomal vincristine or vinblastine targeted by an anti-HER2 scFv were more efficacious than their respective non-targeted formulations or the free drug, in an animal model of breast cancer [86]. Messerschmidt et al demonstrated a new way of delivering tumor necrosis factor (TNF) to tumor cells expressing the fibroblast activation protein (FAP), using TNF-functionalized lipidic nanoparticles that are targeted by an anti-FAP scFv [95]. Hence, data are emerging to demonstrate that targeting of liposomal drugs by scFv results in increased therapeutic effects over non-targeted liposomal drugs and suggest that scFv is a viable alternative to Fab′ or mAb.…”
Section: Efficacy Of Immunoliposomal Drugs Targeted By Means Of Scfvmentioning
confidence: 99%